PERBEDAAN METODE CBT DENGAN ELIP TERHADAP POST PARTUM BLUES PADA URBAN SUKU MADURA - Elly Dwi Masita; Adenia Dwi Ristanti (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
In Asia 20% -60% of post-partum mothers experience post partum blues of 1000 live births, whereas in Indonesia it reaches 15%. Preliminary studies conducted in February 2020 in northern Surabaya with the aim of puerperal women showed that 27 out of 33 postpartum mothers showed symptoms of post partum blues with various levels. This figure means that 81% of women giving birth experience post partum blues. The purpose of this study was to determine the differences between the CBT and ELIP methods on the post partum blues degree in urban Madura in Surabaya. The type and method of this research is quantitative with an experimental approach of non equivalent control group desaign. The population was 60 postpartum mothers. Sampling used a total sampling of 30 as pre and post CBT groups and 30 as pre and post ELIP groups. Instrument using EPDS with a score> 5 through online screening Instrument using Edinburgh Post Partum Depression Scalae (EPDS), SOP, Check List. Test using pair T test with p> 0.05.Results: There were differences in the pre and post groups in each of the CBT and ELIP groups. In the CBT group there was a decrease in the post partum blues degree by 24.86. Whereas in the ELIP group there was a decrease in the degree of post partum blues by 16.62 after being given treatment, while the results of the paired t test showed p = 0.001 in the CBT and ELIP groups which meant that there was an influence of the CBT and ELIP methods on the post partum blues degree. Conclusion: Paired t-test found that there was a significant difference in mean between the pre and post groups both CBT and ELIP methods.